Gestão integrada da zona costeira como subsídio ao planejamento e ordenamento territorial de Flecheiras, Trairi, Ceará - Oliveira, Victor Hugo Holanda (2019)
The concern with the socio-environmental quality of the coast has become a constant in recent years, so that new policies for the preservation and conservation of these environments have been disseminated in the search for a better relationship between society and the space in which it lives. Disordered occupation processes, the intensification of large economic activities, such as tourism, summer and energy production, are some of the vectors that greatly alter the dynamics of coastal environments, without a proposition local character planning. Based on the premise that the coast is already occupied, the Integrated Management of the Coastal Zone (GIZC) presents itself as a subsidy tool for planning and territorial planning policies, aiming at the management of coastal spaces, favoring the preservation of conservation and economic development in a sustainable way. Thus, the research proposes to analyze the delimited area as Flecheiras, located in the municipality of Trairi, West Coast of Ceará, based on a discussion about the reasons that drove the occupation process, characterizing the main aspects environmental and urban network, in addition to the identification of scenarios of use and occupation, seeking the indication of measures of planning and management of the local territory. For this research, it was necessary to collect historical, cartographic and bibliographic data from the area, in addition to the use of Geographic Information Systems (GIS) and the GIZC methodology to help in the delimitation of environmental systems, recognition of the existing urban network and the projection of development scenarios. Thus, based on the research conducted, it is observed that Flecheiras, due to their landscape beauties, natural and economic potentialities, had an accelerated process of occupation, which altered its dynamism which suggests the proposition of planning, planning and management policies of the territory, seeking the improvement of environmental quality and sustainable development for the area.